Modeling Above-Ground Biomass Across Multiple Circum-Arctic Tundra Sites Using High Spatial Resolution Remote Sensing Data - Räsänen, Tuomas Aleksi; Juutinen, Sari Anneli; Aurela, Mika; Virtanen, Tarmo (2018)
Non peer reviewed